Effects of cannabinoids on resting state functional brain connectivity: A systematic review. (February 2023) - Lorenzetti, Valentina; Gaillard, Alexandra; Thomson, Diny; Englund, Amir; Freeman, Tom P.
Abstract: Cannabis products are widely used for medical and non-medical reasons worldwide and vary in content of cannabinoids such as delta-9-tetrahydrocannabinol (THC) and cannabidiol (CBD). Resting state functional connectivity offers a powerful tool to investigate the effects of cannabinoids on the human brain. We systematically reviewed functional neuroimaging evidence of connectivity during acute cannabinoid administration. A pre-registered (PROSPERO ID: CRD42020184264) systematic review of 13 studies comprising 318 participants (mean age of 25 years) was conducted and reported using the PRISMA checklist. During THC and THCv exposure vs placebo reduced connectivity with the NAcc was widely reported. Limited evidence shows that such effects are offset by co-administration of CBD. NAcc-frontal region connectivity was associated with intoxication levels. Cannabis intoxication vs placebo was associated with lower striatal-ACC connectivity. CBD and CBDv vs placebo were associated with both higher and lower connectivity between striatal-prefrontal/other regions. Overall, cannabis and cannabinoids change functional connectivity in the human brain during resting state as a function of the type of cannabinoid examined. Highlights: Cannabis and cannabinoids alter rsFC as a function of the cannabinoid examined. In THC intoxication vs placebo reduced connectivity with the NAcc was reported. Limited evidence shows that such effects are offset by co-administration of CBD.